Human Capital, Education, and Sustainability - Donald Gillies (Universidade de Lisboa, 2014)
Human capital theory remains a powerful influence in modern economics and withineducational discourse. In this paper, the theory and its prevalence across Europeanstate education policy is explored and critiqued in a number of ways includingits implication in an ethos which aims at maximising returns from resources. Assuch, the theory and its practical manifestations are inimical to the concerns ofsustainability. The paper suggests that while the concept of "natural capital", in itsfocus on the need to preserve profitable natural resources for future benefit, doescoalesce with sustainability discourse at points, more fruitful potential for thegoals of sustainability lies in redirecting the aims of state education, away from ahuman capital theory orientation, towards a renewal of the social aims inherent inthe original democratic ideals of liberal education.